Multibeam Sonar Ray-Tracing Uncertainty Evaluation from a Hydrodynamic Model in a Highly Stratified Estuary. Issue 4 (3rd July 2020) - Church, Ian William
Abstract: The Port of Saint John is a highly stratified, hyper-tidal estuary that requires frequent hydrographic surveys to ensure that minimum under-keel clearances are maintained and to monitor dredge operations. The potential achievable accuracy and efficiency of a multibeam sonar survey correlates to the knowledge of the physical oceanographic conditions of the harbour. A high-resolution baroclinic hydrodynamic model of the Port of Saint John was constructed to understand the dynamic physical oceanographic environment over four periods representing the limits in river flow conditions. The model provides time-varying outputs of temperature and salinity at predefined depth intervals over the domain. Sound speed is derived from the model output and is used for ray-tracing multibeam sonar data and survey planning to minimize refraction errors. Ray-tracing depth error statistics are calculated from Moving Vessel Profiler (MVP) temperature and salinity casts and used to evaluate the model skill. Results demonstrate that the model can be used to replace observed sound speed profiles and stay within depth accuracy specifications within a swath width of 60 degrees, or more, for most of the year throughout the harbour. Uncertainty increases for swath widths of more than 55 degrees during the most severe stratification of the spring freshet.